Corrosion resistance of ZrNxOy thin films obtained by rf reactive magnetron sputtering - Ariza, E. (2004)
The main aim of this work is the investigation of the corrosion resistance of single layered zirconium oxynitride, ZrNxOy, thin films in artificial sweat solution at ambient emperature. The films were produced by rf reactive magnetron sputtering, using a pure Zr target at a constant temperature of 300 8C. Two different sets of samples were produced. In the first set of films, the substrate bias voltage was the main variable, whereas in the second set, the flow rate of reactive gases (oxygen/nitrogen ratio) was varied. The control of the amount of oxygen allowed the film properties to be tailored from those of covalent zirconium nitride to those of the correspondent ionic oxide. The corrosion behaviour was evaluated by potentiodynamic polarization and Electrochemical Impedance Spectroscopy (EIS) tests. The analysis of EIS data provided detailed information of the corrosion processes occurring at the surface of the system throughout the immersion time. The modifications of the coating microstructure and/or chemical composition induced by the variation of the deposition parameters were also evaluated and correlated with the corrosion mechanisms occurring in each system.